PUBLIC-PRIVATE PARTNERSHIP AS A TOOL FOR INFRASTRUCTURAL RECOVERY OF UKRAINIAN CITIES - V. V. Kruhlov (Pressing Problems of Public Administration, 2022)
Modern needs, the impact of digitalization on social relations and environmental approaches imply increased requirements for the quality and manufacturability of infrastructure facilities. The Russian military aggression inflicted large-scale economic and humanitarian losses on Ukraine, significantly destroying critical infrastructure and social facilities, which will require huge efforts to restore them with the involvement of private sector resources. Public-private partnership (PPP) is a promising tool for implementing the tasks of the public sector. The implementation of PPP projects is based on the formation of appropriate areas for ensuring the institutional environment, which should contribute to the formation of conditions for the development of partnerships between the state and the private sector in the field of legal regulation, institutions, operational experience, investment and business climate, financing. The restoration of infrastructure in Ukraine based on an innovative vision, environmental standards and the needs of the digital society takes into account strategic documents. The main approaches to building infrastructure concern the formation of a Smart City, promoting sustainable and safe operation through common interconnections. The city’s strategy takes into account the needs of digitalization and the concept of sustainable development. It is necessary to highlight the factors of urban space formation (economy, human capital, social cohesion, management, planning and technology). The implementation of innovative infrastructure projects using public-private partnership models will accelerate the post-war reconstruction of Ukrainian cities, attract additional financial and human resources, take into account environmental, innovative and other requirements for modern infrastructure.